Solutions for safe and sustainable management of Vietnam’s public debt - Nguyen, Thanh Cai (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Safe and sustainable public debt is when a country’s debt repayment obligations are paid in full and in a timely manner without resorting to handling measures such as new loans, old repayments, debt extension. . . In the recent period, the safety indicators of Vietnam’s public debt were kept within the allowable limits. However, in recent years, the government’s balance of revenue to repay debt is still difficult, with many potential risks. By collecting published data, statistics, analysis, synthesis, comparison. The article has assessed the current state of public debt safety in the period 2010-2020, on that basis, some management solutions are proposed to ensure the safety and sustainability of public debt in the immediate period.